Reviews - Carolyn E. Hill; Michael Kuhne; Felicia M. Briscoe; Hanna Berger; Candace Walworth (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
Reviews Carolyn E. Hill. Token Professionals and Master Critics: A Critique of Orthodoxy in Literary Studies. (James Sosnoski, 1994). Michael Kuhne. Releasing the Imagination: Essays on Education, the Arts, and Social Change. (Maxine Greene, 1995). Felicia M. Briscoe. Artwork of the Mind: An Interdisciplinary Description of Insight and the Search for it in Student Writing. (Mary M. Murray, 1996). Hanna Berger. If You Want to Write: A Book about Art, Independence and Spirit. (Brenda Ueland, 1997). Candace Walworth. The Rag and Bone Shop of the Heart: Poems for Men. (Robert Bly, James Hillman, Michael Meade, Eds., 1992).